Mitochondrial Genetic Diversity, Population Structure and Detection of Antillean and Amazonian Manatees in Colombia: New Areas and New Techniques - Caballero, Susana; Ortiz-Giral, Maria Camila; Bohorquez, Laura; Lozano Mojica, Juan Diego; Caicedo-Herrera, Dalila; Arévalo-González, Katherine; Mignucci-Giannoni, Antonio A. (Frontiers in Genetics, 2021)
The Antillean manatee (Trichechus manatus manatus) and the Amazonian manatee (Trichechus inunguis) are distributed in rivers in the Caribbean and Amazonian region of Colombia respectively. For 30 years, genetic information has been obtained from these populations in order to inform conservation programs for these endangered species and decide on the location to release them back to the wild. However, in previous studies, samples from rivers in some areas of the country were not included, given the difficulties to access these regions due to either logistic or safety issues. In this study, we analyzed mitochondrial DNA (mtDNA) control region (CR) sequences of from samples of T. manatus manatus (n=37) and T. inunguis (n=4) (410 and 361 bp, respectively), obtained in new and previously unexplored rivers and bays in the country, including the Santa Marta, Urabá Gulf, Ayapel Marsh (San Jorge River Basin), Meta River and Magdalena Medio and the low Magdalena River (Cesar Province and Canal del Dique) as well as additional samples from Puerto Nariño in the Colombian Amazon. Our results included the discovery of two newly described mtDNA CR haplotypes for T. manatus manatus. In addition, we confirmed significant population differentiation at the mitochondrial level between the Magdalena and Sinú rivers and differentiation among areas of the same river, including the middle and low Magdalena River. This differentiation may be related to anthropic changes in the river since construction of the Canal del Dique in the XVI century. We also tested environmental DNA sampling and analyses techniques to evaluate its potential use for manatee detection and monitoring in bodies of water in Colombia, in order to evaluate new areas for future manatee conservation initiatives. We emphasize the need to continue using genetic information to provide evidence on the potential best locations to undertake animal release to prevent outbreeding depression.